Financial Restructuring and its Impact on Operating Performance in the Energy Sector in India - Joshi, Nisarg A.; Desai, Jay (Indian Journal of Finance, 2019)
Purpose: The purpose of this paper was to analyze the impact of restructuring on operating performance of acquiring/restructured energy sector firms in India. This paper attempted to analyze whether there had been a significant difference in the operating performance of the firms in the post-restructuring period. Design/Methodology/Approach: This study included a sample of 43 firms of energy sector and related sub-sectors in India who had undergone financial restructuring. This study involved a two stage methodology. In the first part, paired sample t - test was used to investigate the significant differences in various financial ratios in the pre and post-restructuring period. In the second part of methodology, the focus was given to check the impact of restructuring on the operating performance of the companies in the post-restructuring period using various techniques like factor analysis, correlation matrix, and multiple regression analysis. Findings : The results showed that there was a significant difference in three financial parameters in the pre and post-restructuring period as per the paired t - test. It was also found that there was a significant impact of restructuring on operating performance of firms in all the factors except turnover. Practical Implications: These results are recommended to financial institutions, banks, and executives. This study may also be used for evaluating the reasons behind restructuring and to check whether restructuring creates value or not. This study can also be used to analyze the shift in the structure after restructuring. Originality/Value: The study found that restructuring leads to improvement in the operating performance of the firms after restructuring in the short-term as well as long-term.